UPAYA PENINGKATAN PRESTASI BELAJAR MATA PELAJARAN IPS DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS INKLUSI DI SMP - Suharti; Agus Basuki (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
Social Studies learning in the inclusive Grade VII.A classroom at SMP Negeri 2 Kombeng showed low learning outcomes because instruction remained teacher-centered, student participation was limited, and the learning strategies had not accommodated the diverse characteristics and abilities of students, including those with special educational needs. This study aimed to improve Social Studies learning outcomes through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model. The study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model and was conducted in three cycles. The participants consisted of 28 students, including 27 regular students and one student with special educational needs. Data were collected through learning outcome tests, classroom observations, and documentation, and were analyzed using quantitative and qualitative techniques. The results indicated that the average learning outcomes improved from 65.00 in Cycle I to 70.75 in Cycle II and 75.38 in Cycle III. Classical learning mastery also increased from 60.71% to 75.00% and reached 85.71%. These findings demonstrate that the implementation of the STAD cooperative learning model effectively improved students' Social Studies learning outcomes, classroom participation, and the overall quality of learning in an inclusive classroom. ABSTRAK Pembelajaran Ilmu Pengetahuan Sosial (IPS) di kelas VII.A inklusi SMP Negeri 2 Kombeng menunjukkan hasil belajar yang masih rendah karena pembelajaran masih berpusat pada guru, partisipasi siswa belum optimal, serta strategi pembelajaran belum mampu mengakomodasi keberagaman karakteristik dan kemampuan peserta didik, termasuk siswa berkebutuhan khusus. Penelitian ini bertujuan meningkatkan hasil belajar IPS melalui penerapan model pembelajaran kooperatif tipe Student Teams Achievement Division (STAD). Penelitian menggunakan metode Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart yang dilaksanakan dalam tiga siklus. Subjek penelitian berjumlah 28 siswa yang terdiri atas 27 siswa reguler dan 1 siswa berkebutuhan khusus. Data dikumpulkan melalui tes hasil belajar, observasi, dan dokumentasi, kemudian dianalisis secara kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa rata-rata hasil belajar meningkat dari 65,00 pada Siklus I menjadi 70,75 pada Siklus II dan 75,38 pada Siklus III. Ketuntasan belajar klasikal juga meningkat dari 60,71% menjadi 75,00% dan mencapai 85,71%. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran kooperatif tipe STAD mampu meningkatkan hasil belajar IPS, partisipasi siswa, dan kualitas pembelajaran pada kelas inklusi.